Prospects and problems of the revival of a medicinal plant in the Aral Sea region - Khozhambergenova P (Zien Journals, 2025)
It is necessary to create a single base of scientific research on the cultivation and processing of medicinal plants in the territory of our republic, to study the advanced scientific developments of foreign countries, to establish cooperation with leading scientific institutions, to introduce modern technologies and scientific developments to the republic, and to strengthen the effective use of existing opportunities. For this purpose, scientific research was conducted on this topic.
Keywords: Medicine; alkaloids; agrotechnology